Impact of dietary Spirulina on performance, antioxidant status, carcass traits and pathological alteration in broilers exposed to ochratoxin A stress - Ayman S. Salah; Mahmoud S. El-Tarabany; Marwa Mostafa; Rania Samir Zaki; Mahmoud M. Azzam; Omnia I. El Euony; Mahmoud Alagawany; Antonia Lestingi; Ahmed A. Elolimy; Mahmoud Madkour; Ahmed Fotouh (Frontiers in Veterinary Science)
IntroductionThis study examined the influence of Spirulina platensis, ochratoxin A (OTA), and their combination on growth, antioxidant status, liver and kidney functions, immunity, and carcass traits of broiler chickens.Methods160 unsexed 1-day broiler chicks were divided into four treatment groups, each consisting of 4 replications of 10 chicks. The duration of this study was six weeks, during which the experimental groups were organized as follows: G1 consumed a basal diet (control), G2 consumed a basal diet treated with OTA at a level of 1 mg/kg of diet, G3 consumed a basal diet treated with Spirulina platensis at a level of 1 g/kg of diet, G4 consumed a basal diet treated with OTA at a level of 1 mg/kg of diet and Spirulina platensis at a level of 1 g/kg diet.Results and discussionThe results illustrated that OTA-contaminated feed resulted in a significant elevation in total cholesterol, triglyceride, low- and very low density lipoprotein, and malondialdehyde, along with a significant reduction in antioxidant status and immunological response. On the other hand, Spirulina supplementation significantly enhanced performance performance (body weight, body weight gain and feed conversion ratio). Lipid profile was significantly decreased by Spirulina supplementation. Antioxidant activity (superoxide dismutase, catalase, total antioxidant capacity, and glutathione peroxidase) of broilers exposed to OTA was significantly increased by Spirulina supplementation. Finally, supplementing Spirulina platensis in broiler chickens fed on OTA contaminated diet attenuated the harmful effects of OTA, while improving the growth performance, antioxidant activity, lipid profile, and immune response of broiler chickens.